2021
DOI: 10.1016/j.omtn.2021.07.013
|View full text |Cite
|
Sign up to set email alerts
|

5′-tiRNA-Cys-GCA regulates VSMC proliferation and phenotypic transition by targeting STAT4 in aortic dissection

Abstract: Accumulating evidence shows that tRNA-derived fragments are a novel class of functional small non-coding RNA; however, their roles in aortic dissection (AD) are still unknown. In this study, we found that 5 0 -tiRNA-Cys-GCA was significantly downregulated in human and mouse models of aortic dissection. The abnormal proliferation, migration, and phenotypic transition of vascular smooth muscle cells (VSMCs) played a crucial role in the initiation and progression of aortic dissection, with 5 0 -tiRNA-Cys-GCA as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Oxidative stress is an abnormal physiological phenomenon, and it is defined as "an imbalance between antioxidants and oxidants, resulting in the disruption of redox signaling and the corresponding molecular damage." To the best of our knowledge, it is associated with nearly all diseases such as cancers (Hayes et al, 2020), cardiovascular diseases (Dubois-Deruy et al, 2020), aortic dissection (Zong et al, 2021), atherosclerosis Xue et al, 2021), COVID-19 , drug-induced injuries , and diabetes (Zhang et al, 2020). The effective regulation or relief of oxidative stress can potentially prevent many diseases, and EVs play an important role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is an abnormal physiological phenomenon, and it is defined as "an imbalance between antioxidants and oxidants, resulting in the disruption of redox signaling and the corresponding molecular damage." To the best of our knowledge, it is associated with nearly all diseases such as cancers (Hayes et al, 2020), cardiovascular diseases (Dubois-Deruy et al, 2020), aortic dissection (Zong et al, 2021), atherosclerosis Xue et al, 2021), COVID-19 , drug-induced injuries , and diabetes (Zhang et al, 2020). The effective regulation or relief of oxidative stress can potentially prevent many diseases, and EVs play an important role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial cells (VECs) are the predominant cell type and generate a continuous inner monolayer of blood vessels, which are responsible for regulating inflammation and vascular homeostasis in healthy blood vessels (Coultas et al, 2005). Also, the attachment of monocytes to VECs is vital for the occurrence of atherosclerosis and inflammation (Rajendran et al, 2013;Yang et al, 2019;Li et al, 2021a;Li et al, 2021b;Zong et al, 2021). Herein we hypothesize that FD-based nanofibers would be able to exhibit favorable physicochemical properties to mediate VEC responses in engineering vascular tissues.…”
Section: Introductionmentioning
confidence: 99%
“…More studies have shown the regulatory role of ncRNA in health and disease (47,48). miRNA is a key regulator of cardiac phenotype that has caught the attention of basic scientists and clinicians (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%